Conjunctival and nasal microbiota evaluation of dogs submitted to dacryocystorhinostomy - Joelson Arruda Jardim; Marcela Fernanda Moretti; Alexandre Lima de Andrade (Semina: Ciências Agrárias, 2023)
The purpose of this study was to evaluate changes in the conjunctival and nasal microbiota, in the long term, of dogs undergoing bilateral dacryocystorhinostomy. Twelve male and female dogs (23 eyes), aged between 1 and 10 years, were enrolled in the study, selected on the basis of presentation with epiphora and chromodacryorrhea for at least six months. Cultures of material obtained from the ocular conjunctiva and nasal sinus of all dogs were evaluated to determine the conjunctival and nasal microbiota pre-and postoperatively (at 60, 120, and 240 d). Preoperatively, gram-negative bacteria were identified in the conjunctival microbiota of 66.5% (n=8), while gram-positive bacteria were found in 33.3% (n=4). Throughout the clinical evolution, a balance was found between the presence of gram-positive and gram-negative bacteria in the conjunctival microbiota. Pure cultures of Pseudomonas aeruginosa (25%) and Staphylococcus intermedius (25%) were found most frequently. Regarding the conjunctival microbiota, we can conclude that in obstructive diseases, there is a predominance of gram-negative bacteria in the lacrimal system, notably Pseudomonas aeruginosa. This study did not observe an increase in bacterial counts in the nasal cavity through the new surgical pathway to the conjunctival sac.